2007
DOI: 10.1159/000111072
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback for Endothelial Apoptosis: A Potential Physiological Role for Fibroblast Growth Factor

Abstract: Although most physiologically important processes are regulated through negative feedback loops and numerous factors regulating endothelial apoptosis are identified, little is known about negative feedback mechanisms for endothelial apoptosis. Here we describe the release of soluble anti-apoptotic activity by endothelial cells undergoing apoptosis, and identify fibroblast growth factor-2 (FGF-2) as contributing to this. In brief, apoptosis of human umbilical vein endothelial cells was induced by serum deprivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
5
5
0
Order By: Relevance
“…Besides promoting MSC survival and proliferation, the released bFGF stimulated host cell proliferation in the ischemic limb as the density of Ki67+ cells in the Gel/bFGF group was significantly higher than that in the Gel and non-injection groups (Figure 7). These results are consistent with those reported previously that bFGF can inhibit apoptosis of osteoblasts[74] and endothelial cells [75] under ischemic conditions. In these reports, the improved cell survival is a result of bFGF activating osteoblast PI3k/Akt pathway[74] and endothelial cell hypoxia-induced factor-1 (HIF-1) pathway [75], respectively.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Besides promoting MSC survival and proliferation, the released bFGF stimulated host cell proliferation in the ischemic limb as the density of Ki67+ cells in the Gel/bFGF group was significantly higher than that in the Gel and non-injection groups (Figure 7). These results are consistent with those reported previously that bFGF can inhibit apoptosis of osteoblasts[74] and endothelial cells [75] under ischemic conditions. In these reports, the improved cell survival is a result of bFGF activating osteoblast PI3k/Akt pathway[74] and endothelial cell hypoxia-induced factor-1 (HIF-1) pathway [75], respectively.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with those reported previously that bFGF can inhibit apoptosis of osteoblasts[74] and endothelial cells [75] under ischemic conditions. In these reports, the improved cell survival is a result of bFGF activating osteoblast PI3k/Akt pathway[74] and endothelial cell hypoxia-induced factor-1 (HIF-1) pathway [75], respectively. In this work, we demonstrated that the prosurvival effect on MSCs is due to bFGF activating KLF4 pathway, an important protective factor in disease states and mediator to nitric oxide in ischemic tissues (Figure 3).…”
Section: Discussionsupporting
confidence: 94%
“…Although we have interpreted endothelial bFGF release as potentially important for OSF fibrosis, it can equally well be argued that such release would help restore tissue vascularity via endothelial mitogenesis following endothelial necrosis. Related to this, while there was no evidence for arecoline‐induced endothelial apoptosis in any of the current experiments described, or in our previous work , it is interesting that bFGF inhibits HUVEC apoptosis ; endothelial apoptosis is induced upon bFGF withdrawal ; and apoptotic endothelium exerts negative feedback for further apoptosis via release of bFGF . On this basis, evolution may have selected for a comparable bFGF‐mediated mechanism to both restore vascularity following toxic injury and to limit excessive endothelial apoptosis during tissue remodeling.…”
Section: Discussionmentioning
confidence: 50%
“…Cell survival was established by direct cell counts of remaining adherent cells, accepted as providing an unambiguous measure for endothelial survival . Results of cell counting experiments were essentially paralleled by those of the LDH and MTT assays, indicating the absence of a clear effect of arecoline at levels insufficient to cause cell death, on either plasma membrane integrity or NADH production by mitochondria.…”
Section: Discussionmentioning
confidence: 98%